Studi Gaya Desain Interior Museum Karya Daniel Libeskind - Hermanto, Meliana (Intra, 2013)
Daniel Libeskind is one of architect that implement decontructive style in design his building and well known for itâs bold form. Decontructive can be trace as one of modern architectureÂ branch that sometimes used as alternative style outside the boredome of modern architecture. Libeskindâs work is considered different from most architect, which clearly seen in some of museum he worked on. In every part of his design, form consistency and philosophy approach is a must. Itâs what make Libeskind workÂ has deep meaning. He prefer to deliver strong message and impresionÂ to the beholder through hisÂ design.